The Ethics of Transhumanism from the Perspective of Gilbert Ryle Monist Ethics: Ambiguities and Prospects - Simanjuntak, Mardohar Batu Bornok; Doweng Bolo, Andreas; Loho, Ambrosius Markus (Sapientia Humana: Jurnal Sosial Humaniora, 2023)
Transhumanism attempts to overcome human limitations through the use of technology, such as nanotechnology, artificial intelligence, and genetic modifications. In the monist ethical perspective, humans are considered complex material entities, and consciousness is understood as a product of the physical and chemical interactions in the brain with various other parts of the body. The problem is that with such artificial revolutions, ethical foundations based on corporeal limitations become irrelevant. Gilbert Ryle questions Platonistic dispositions that overly rely on reduction with the consequence of extractive knowledge rather than abstract knowledge. Plato's line of thought is then strengthened by Cartesian dualism, which, when applied in a monist perspective, can be reduced to an extraction of brain performance. Ryle proposes an abstraction that allows for the interaction between elements to form a unified understanding of the complex. Based on Ryle's thinking, a study of monist ethics can offer a thoughtful approach to constructing an ethical framework that aligns with the transhumanist era's revolution.